Failure analysis of buttress, acme and modified squa re threaded mild steel (is2062) tie rods - THEJA. N; Sreenivasulu Bezawada; S Praveen Kumar (International Journal of Innovations in Engineering Research and Technology, 2021)
Steel tie rods are imperative load bearing capacity segments in applications where high levelsof per stresses are needed. The tie rod bearing capacity hasnot just by the strength of thesegment, but also it depends on the thread strength. Investigation ofthe thread strengthconnections and finding the best possible amount of threads engagement iscrucial to makesure structural protection. In this document the results of tensile rupture experiments on mildsteel IS2062 tie rods having threaded connections like Buttress, ACME and Modified squareexperiment setup provided by jyothi spectro analysis Hyderabad. In this experiment we teston mild steel tie rod specimens to determine ultimate load as well as deformations. Theresults of these experiments suggest the least number of turnsof the thread engagement forprevent the breakdown of threaded mild steel tie rod in realistic applications.